The Pulitzer Air Races American aviation and speed supremacy, 1920-1925 - Gough, Michael (McFarland, 2013)
"This book about the Pulitzer Trophy Air Races highlights businessmen, generals and admirals who saw racing as a way to drive aviation progress, designers and manufacturers who produced record-breaking racers, and dashing pilots. It emphasizes roles played by host communities and analyzes the Pulitzers' importance and why their story has languished in obscurity for 85 years"--